Key performance indicators and leg positioning for the kick-start in competitive swimmers - Burkhardt, D.; Born, D.-P.; Singh, N. B.; Oberhofer, K.; Carradori, S.; Sinistaj, S.; Lorenzetti, S. (Sports Biomechanics, 2023)
The aim of the study was to (1) assess the test-retest reliability of a novel performance analysis system for swimming (KiSwim) including an instrumented starting block and optical motion capture system, (2) identify key performance indicators (KPI) for the kick-start, (3) determine the most beneficial position of the strong leg and (4) investigate the effect of acute reversal of leg positioning. During three sessions, kick-starts of 15 competitive swimmers were investigated. Eighteen kinematic and kinetic parameters showed high reliability (ICC>0.75) from which principal component analysis identified seven KPI (i.e., time to 15 m, time on-block, depth at 7.5 m, horizontal take-off velocity, horizontal impulse back plate, horizontal peak force back plate and vertical peak force front plate). For the preferred start position, the back plate showed a higher horizontal peak force (0.71 vs. 0.96 x body mass; p < 0.001) and impulse (0.191 vs. 0.28Ns/BW; p < 0.001) compared to front plate. Acute reversal of the leg position reduced performance (i.e., increased time to 15 m and reduced horizontal take-off velocity). However, plate-specific kinetic analysis revealed a larger horizontal peak force (p < 0.001) and impulse (p < 0.001) for the back compared to the front plate in any start position investigated. Therefore, swimmers are encouraged to position the strong leg in the back.